Antenatal determination of fetal rhesus (RH) D status using cell free fetal DNA in the maternal circulation before 20 weeks' gestation: is routine application practical and beneficial?. (7th June 2011) - Chitty, L S; Finning, K; Massey, E; Soothill, P; Daniels, G
Abstract : Analysis of free fetal DNA (cffDNA) in D- pregnant womens' blood can predict fetal D type. NICE recommended evaluation of this technology to spare D– women carrying a D– fetus exposure to anti-D, with potential savings to the NHS. Here we describe implementation at 28 weeks and evaluate effectiveness, costs and benefits before 20 weeks. Methods: D- mothers attending seven hospitals in England were invited to have blood taken for cffDNA analysis of fetal RHD status at booking, Down's syndrome screening and the 20 week anomaly scan. If inconclusive or a D+ fetus was predicted, anti-D was given. Mothers predicted to have a D- fetus had repeat cffDNA testing at 28 weeks when it is know to be accurate (Finning BMJ 2008;336 :816–8). Where D- status was confirmed anti-D was withheld. D type was confirmed by cord blood testing. Results: Preliminary results are shown in the table 1 . Conclusions: Implementation of routine cffDNA testing for fetal D status in D- mothers will be possible from 11 weeks gestation with associated reduction in anti-D administration of around 40%. Evidence suggests this will be cost effective and favourably received by mothers who are keen to avoid anti-D if possible.